List of personal names on a ceramic bowl fragment from Siscia - Demicheli, Dino (Array, 2008)
This work contains an onomastic analysis of ten names which were incised on the bottom of the ceramic bowl or plate found in archaeological excavations in Siscia. The emphasis of this paper is on the onomastic analysis which shows that the local people mentioned on the list could have been participants of some Siscian feast. Some of the names, if their reading is correct, are not known so far in the onomastic repertoire of the Empire at all. Also, there was no such graffito inscription found so far in Siscia as well as in Croatia.